Pulmonary microRNA profiles identify involvement of Creb1 and Sec14l3 in bronchial epithelial changes in allergic asthma - Bartel, Sabine; Schulz, Nikola; Alessandrini, Francesca; Schamberger, Andrea C.; Pagel, Philipp; Theis, Fabian J.; Milger, Katrin; Noessner, Elfriede; Stick, Stephen M.; Kicic, Anthony; Eickelberg, Oliver; Freishtat, Robert J.; et al. (Scientific Reports, 2017)
Asthma is highly prevalent, but current therapies cannot influence the chronic course of the disease. It is thus important to understand underlying early molecular events. In this study, we aimed to use microRNAs (miRNAs)-which are critical regulators of signaling cascades-to identify so far uncharacterized asthma pathogenesis pathways. Therefore, deregulation of miRNAs was assessed in whole lungs from mice with ovalbumin (OVA)-induced allergic airway inflammation (AAI). In silico predicted target genes were confirmed in reporter assays and in house-dust-mite (HDM) induced AAI and primary human bronchial epithelial cells (NHBE) cultured at the air-liquid interface. We identified and validated the transcription factor cAMP-responsive element binding protein (Creb1) and its transcriptional co-Activators (Crtc1-3) as targets of miR-17, miR-144, and miR-21. Sec14-like 3 (Sec14l3)-a putative target of Creb1-was down-regulated in both asthma models and in NHBE cells upon IL13 treatment, while it's expression correlated with ciliated cell development and decreased along with increasing goblet cell metaplasia. Finally, we propose that Creb1/Crtc1-3 and Sec14l3 could be important for early responses of the bronchial epithelium to Th2-stimuli. This study shows that miRNA profiles can be used to identify novel targets that would be overlooked in mRNA based strategies.
CRIS-Team Scopus Importer:2023-03-08